Seeing beyond negotiations: the impacts of the Belt and Road on Sino-Kazakh transboundary water management - Brassett, J.; Akmadi, M.; Sternberg, T. (International Journal of Water Resources Development, 2023)
China’s Belt and Road Initiative (BRI) and infrastructural development has led to growing concerns regarding the future of Central Asia’s water resources. However, few attempts have been made to assess the impacts this will have on specific transboundary basins within the region. This article explores how the context of the BRI transcends its physical impacts within the Ili and Irtysh basins, creating a sanctioned discourse that forecloses the possibility of ‘successful’ negotiations at an official level. As such, pathways to transboundary water management that exist beyond the negotiations are shown to have greater plausibility and potential effectiveness.